Perbandingan Sintesis antara Senyawa 4’-Nitrokhalkon dan 2,4- Dimetoksi-4’-Nitrokhalkon dengan Bantuan Iradiasi Gelombang Mikro - Shien, Ong Cong; Soewandi, Ami; Caroline, Catherin (Jurnal Farmasi Sains dan Terapan, 2017)
Chalcone (1,3-diphenylprop-2-en-1-one) is a precursor compound of flavonoids that have two aromatic rings connected by three α, β-unsaturated carbons. Chalcone can be synthesized by the base-catalysed crossed aldol condensation (Claisen-Schmidt) using the reaction between aromatic aldehyde with aryl ketone. In this research, synthesize of 4-nitrochalcone and 2,4-dimethoxy-4’-nitrochalcone compounds with microwave irradiation assistance had been done. 4-nitrochalcone was synthesized from acetophenone and 4’-nitrobenzaldehyde, while 2,4-dimethoxy-4’-nitrochalcone was synthesized from 2,4-dimethoxyacetophenone and 4’-nitrobenzaldehyde. The purity of the synthesis compounds were shown from the data of melting point and thin layer chromatography. Identification of structure was shown from infrared spectral data and proton nuclear magnetic resonance. From the obtained results, 4-nitrochalcone and 2,4-dimethoxy-4’-nitrochalcone compounds can be synthesized by microwave irradiation assistance. The yield of 4’-nitrochalcone was 58.19%, while 2,4-dimethoxy-4’-nitrochalcone was 19.07%. The effect of methoxy groups (-OCH3) on acetophenoe ease the reaction of the formation of chalcone compounds in terms of yield of the synthesis product.